Effects of Components of Servant Leadership on Social Responsibility in the Agricultural Bank of Sistan - Mohammad Mostafa Dahmardeh (Journal of Global Pharma Technology, 2017)
Theory of servant leader is among theories that is developing and has influenced on form and style of leadership in present century. Greenleaf believes that servant leadership is based on philosophy of being servant first. Servant leaders are those mainly focus on serving other people’s highest priority needs and on the growth and well-being of people and the communities to which they belong. So the aim of this research, is reviewing Effects of components of servant leadership on social responsibility of employees of Agricultural Bank of Sistan. Methodology of present research is applicable regarding its aim, descriptive regarding its nature and qualitative in terms of execution method. In this research in order to gather theoretical principles, library study is used.  In order to gather statistical information for research assumption, field research and search in statistical society are used. To gather information, first servant leadership and social responsibility questionnaire is prepared by interviewing experts, elites and professors, then distributed among statistical population and analyzed by SPSS software. Statistical population of this research includes 96 people of all employees of Agricultural Bank of Sistan. To determine sample population, 96 people were selected.  Sampling method is simple random. To review and analyze data, descriptive and inferential statistics were used. At inferential level, linear regression test and step by step were used to show effects servant leadership and its components on social responsibility of employees. Results indicate that servant leadership and its components have meaningful effects on social responsibility of employees. Keywords: Leadership, Servant leadership, Social responsibility, Agricultural Bank.